2015
DOI: 10.1080/15384047.2015.1056945
|View full text |Cite
|
Sign up to set email alerts
|

ElevatedARG1expression in primary monocytes-derived macrophages as a predictor of radiation-induced acute skin toxicities in early breast cancer patients

Abstract: Radiation therapy (RT) the front-line treatment after surgery for early breast cancer patients is associated with acute skin toxicities in at least 40% of treated patients. Monocyte-derived macrophages are polarized into functionally distinct (M1 or M2) activated phenotypes at injury sites by specific systemic cytokines known to play a key role in the transition between damage and repair in irradiated tissues. The role of M1 and M2 macrophages in RT-induced acute skin toxicities remains to be defined. We inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The first gene, ARG1 , catalyzes the hydrolysis of arginine to ornithine and urea and is expressed in macrophages. Interestingly its expression has been found upregulated in vitro , in primary monocytes-derived macrophages obtained from blood samples collected from patients before and after the first delivered 2 Gy radiotherapy dose in breast cancer patients (36). The authors found that the level of ARG1 mRNA significantly correlated with higher grades of radiation-induced acute skin toxicities in early breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…The first gene, ARG1 , catalyzes the hydrolysis of arginine to ornithine and urea and is expressed in macrophages. Interestingly its expression has been found upregulated in vitro , in primary monocytes-derived macrophages obtained from blood samples collected from patients before and after the first delivered 2 Gy radiotherapy dose in breast cancer patients (36). The authors found that the level of ARG1 mRNA significantly correlated with higher grades of radiation-induced acute skin toxicities in early breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…34 After differentiation into macrophages, cells were stimulated with LPS (lipopolysaccharide; 100 ng/mL) plus IFN (interferon) γ (50 ng/mL) or vehicle (0.1% BSA) for 48 hours. 35,36 Then, the cellular RNA was collected, and reverse transcribed into cDNA. qPCR was performed to detect the expression of M1 macrophage markers.…”
Section: Monocyte Isolation and M1 Polarization Of Macrophagesmentioning
confidence: 99%
“…2018) and its elevated expression indicates radiation therapy‐induced acute skin toxicities (Jung et al . 2015). Gene FGF23 acts as a proinflammatory cytokine, and its high expression is associated with an increased risk of mortality, probably because of its contribution to decreased host defense response to infection, left ventricular hypertrophy, inflammation and anemia (Courbebaisse & Lanske 2017).…”
Section: Figurementioning
confidence: 99%
“…Gene ARG1 catalyzes the conversion of L-arginine to L-ornithine and urea, is considered an oncogene in hepatocellular carcinoma (You et al 2018) and its elevated expression indicates radiation therapy-induced acute skin toxicities Figure 2 Differential network analysis. Topological differences in gene coexpression networks between pigmented and non-pigmented samples: GO terms pigmentation (GO:0043473), melanosome (GO:0042470) and defense response to bacterium (GO:0042742) (Jung et al 2015). Gene FGF23 acts as a proinflammatory cytokine, and its high expression is associated with an increased risk of mortality, probably because of its contribution to decreased host defense response to infection, left ventricular hypertrophy, inflammation and anemia (Courbebaisse & Lanske 2017).…”
mentioning
confidence: 99%